Practical Educational Experience of the Children's Choreographic Association "School-Studio Remix" Activity as an Example of the Development of Professional Competencies in Gifted Teenagers - Chekmazova O. Y. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the aspects of the influence of choreography on the internal emotional state of the teenager are considered in the article. A special role is given to improvisation as a separate direction in learning. Dance training is considered a complex creative process. The stages of educational dance activity are revealed.
Keywords: педагог; преемственность; творчество; creativity; task; teacher; импровизация; задача; хореография; одаренные учащиеся; choreography; gifted teenagers; continuity; improvisation